2020
DOI: 10.31235/osf.io/rq8sn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escaping to nature during a pandemic: A natural experiment in Asian cities during the COVID-19 pandemic with big social media data

Abstract: Cities implemented social distancing measures to cope with COVID-19, which kept people away from nature. A steep drop in the greenspace use was observed in western cities. Surprisingly, news revealed a surging greenspace use in Asian cities. In this study, we used COVID-19 outbreak stages as natural experiments to investigate individual behavioural changes of greenspace use before and during the pandemic. Our case cities are Hong Kong, Singapore, Tokyo and Seoul. We extracted panel data which consisted of long… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…Half of the participants indicated going into nature more often than before C19CM. These findings complement research elsewhere in Europe (17,39) and Asia (16).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Half of the participants indicated going into nature more often than before C19CM. These findings complement research elsewhere in Europe (17,39) and Asia (16).…”
Section: Discussionsupporting
confidence: 86%
“…Previous research highlighted that contact with nature may be an effective strategy to cope with stress (11,12) and emotion regulation (13). During the pandemic, a trend of people visiting nature more often could be observed in western countries (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Both outdoor recreation [ 87 ] and nature exposure [ 88 , 89 ] can improve psychosocial and eudaimonic well-being [ 90 , 91 ]. Recent studies of people across the world show protective psychological effects of park and green space access during the pandemic [ 92 ] as well as lower rates of infection and mortality [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that people have used UGS more since the pandemic started ( Grima et al, 2020 ; Kleinschroth and Kowarik, 2020 ; Lu et al, 2020 ; Venter et al, 2020 ). Our survey respondents visited UGS multiple times per week on average, but respondents were equally likely to increase or decrease their UGS visits during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Many cities, regions, and entire countries enacted temporary lockdowns (in addition to social distancing recommendations and mandates) to control the spread of the virus, leading to unprecedented reductions in mobility ( Rutz et al, 2020 ) and temporary closure of public spaces ( Slater et al, 2020 ). Some studies have found increases in park and natural area use during the pandemic, as residents seek relief from rising stress and anxiety and try to limit indoor activities with higher virus transmission risk ( Grima et al, 2020 ; Kleinschroth and Kowarik, 2020 ; Lu et al, 2020 ; Venter et al, 2020 ). However, limited physical or perceived access to UGS, due to either lack of nearby greenspace, closed facilities, or perceptions of not being welcome in UGS, could prevent people from using UGS during this crisis.…”
Section: Introductionmentioning
confidence: 99%